Implementasi Manajemen Perubahan Pada Pondok Pesantren Di Pesantren Ulumul Qur'an Stabat Kabupaten Langkat - Yuda Mulia Ramadhan Sitepu, Muhammad Fuad Zaini (CV. PUSDIKRA MITRA JAYA, 2021)
This study is to see the implementation of change management in Islamic boarding schools at Ulumul Qur'an Islamic boarding school Stabat, Langkat Regency. the method used is qualitative. The results of the study show that the implementation of change management in Islamic boarding schools at the Ulumul Qur'an Islamic boarding school Stabat, Langkat Regency, has a history of its establishment, the existence of educators and education staff, the supporting factors in the management of change in the pesantren and the inhibiting factors in the management of change in the pesantren. . From the history of the establishment of the Ulumul Qur'an Islamic boarding school, we can see that this Islamic boarding school prioritizes the Qur'anic Sciences, educators and education staff who really have achievements to teach at the Ulumul Qur'an Islamic boarding school, then there are supporting factors for the pesantren. here is the input from community leaders, parents and the number of students where the pesantren can experience good changes and finally the inhibiting factor in the pesantren is also when the state of the cottage or the financial situation is starting to need and there are shortages, here we will also affect the management factor and because it is all based on ability in terms of financial efforts